STRATEGY OF THE DEPARTMENT OF COMMUNICATION, INFORMATICS, COPYRIGHT AND STATISTICS OF CENTRAL KALTENG PROVINCE IN DEVELOPING THE INFORMATION COMMUNITY (KIM) - Eka Muliyanti; Srie Rosmilawati (RADJA PUBLIKA, 2025)
This study examines the efforts of the Office of Communication, Informatics, Encryption, and Statistics of Central Kalimantan Province in fostering and strengthening Community Information Groups (Kelompok Informasi Masyarakat/KIM) as community-based public communication partners. Using a qualitative approach with a descriptive method, supported by in-depth interviews with key informants namely a Senior Public Relations Officer of the Office of Communication, Informatics, Encryption, and Statistics of Central Kalimantan Province and a KIM activist in Central Kalimantan, the Chairperson of KIM Bintang Jaya Itah this research explores how the provincial government carries out capacity building, institutional development, and improvements in digital infrastructure to enhance KIM performance in disseminating public information. The findings show that government support is manifested through structured training in public communication, digital literacy, and citizen journalism; continuous mentoring in the use of platforms such as kim.id and KIM Digital; and the implementation of tiered coordination involving KIM networks at the provincial, district, sub-district, and village levels. Diskominfosantik has institutional duties and functions in the fields of public communication, informatics, and information dissemination. KIM is one of the strategic programs that serves as an instrument for community-based information empowerment, making this topic relevant to the role of government institutions. Studies related to KIM in Central Kalimantan are still relatively limited; therefore, this research provides a new contribution in the context of developing community information institutions at the regional level. Although various initiatives have been implemented, several challenges remain, such as limited community management capacity among KIM implementers, uneven digital skills, and a relatively high dependence on government facilitation to support operational activities. This study shows that effective collaboration and role-sharing in producing content relevant to local needs are essential. The Office of Communication, Informatics, Encryption, and Statistics of Central Kalimantan Province acts not only as a regulator but also as a facilitator, mentor, and community empowerer in the field of information.Overall, this study concludes that government efforts through the Office of Communication, Informatics, Encryption, and Statistics of Central Kalimantan Province in the development of Community Information Groups (KIM) fall into the effective category and encourage KIM to be more active in producing and disseminating information. In the era of hoaxes and disinformation, the government requires trustworthy community-based information channels, and KIM represents one such solution; however, there are still KIMs that remain inactive in certain regions or districts and therefore require further attention and guidance.